H0 from cosmic chronometers and type Ia supernovae, with Gaussian processes and the novel weighted polynomial regression method - Gómez-Valent, Adrià; Amendola, Luca (Journal of cosmology and astroparticle physics, 2018)
In this paper we present new constraints on the Hubble parameter H 0 using: (i) the available data on H ( z ) obtained from cosmic chronometers (CCH); (ii) the Hubble rate data points extracted from the supernovae of Type Ia (SnIa) of the Pantheon compilation and the Hubble Space Telescope (HST) CANDELS and CLASH Multy-Cycle Treasury (MCT) programs; and (iii) the local HST measurement of H 0 provided by Riess et al. (2018), H 0 HST =(73.45±1.66) km/s/Mpc. Various determinations of H 0 using the Gaussian processes (GPs) method and the most updated list of CCH data have been recently provided by Yu, Ratra & Wang (2018). Using the Gaussian kernel they find H 0 =(67.42± 4.75) km/s/Mpc. Here we extend their analysis to also include the most released and complete set of SnIa data, which allows us to reduce the uncertainty by a factor 3 with respect to the result found by only considering the CCH information. We obtain H 0 =(67.06± 1.68) km/s/Mpc, which favors again the lower range of values for H 0 and is in tension with H 0 HST . The tension reaches the 2.71σ level. We round off the GPs determination too by taking also into account the error propagation of the kernel hyperparameters when the CCH with and without H 0 HST are used in the analysis. In addition, we present a novel method to reconstruct functions from data, which consists in a weighted sum of polynomial regressions (WPR). We apply it from a cosmographic perspective to reconstruct H ( z ) and estimate H 0 from CCH and SnIa measurements. The result obtained with this method, H 0 =(68.90± 1.96) km/s/Mpc, is fully compatible with the GPs ones. Finally, a more conservative GPs+WPR value is also provided, H 0 =(68.45± 2.00) km/s/Mpc, which is still almost 2σ away from H 0 HST .
Im Titel ist die Zahl 0 nach H tiefgestellt
Gesehen am 24.11.2020